(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study investigates how social media marketing (SMM) and electronic word-of-mouth (eWOM) influence cosmetic and fashion brand preferences among female undergraduate students in Ikot Ekpene, Nigeria. The study was hinged on the Uses and Gratifications (U&G) theory. The study employed a survey research design with a sample of 388 students drawn from Ritman University and Akwa Ibom State Polytechnic. Findings revealed that 70.1% of respondents reported high awareness of cosmetic and fashion brand marketing on social media, while 61.6% were confident in using these platforms to discover such brands. Engagement was moderately strong, with 55.6% actively interacting with brand content and 47.9% indicating continued interest. However, 33.7% were unwilling to maintain ongoing engagement. Factors influencing brand preference included perceived product quality (52.8%), transactional security (55.2%), and convenience (46.4%). Trust in online brands was more divided, with 47.9% expressing trust and 39.2% expressing distrust. Furthermore, brand preference was most influenced by delivery options (63.9%) and online reviews (53.3%). These findings indicate that while SMM and eWOM effectively enhance awareness and engagement, trust remains a critical barrier. The study recommends that brands prioritise trust-building mechanisms, personalised messaging, and platform-specific strategies to better engage digitally active youth consumers in semi-urban contexts